THE TECHNIQUE OF PERSPECTIVE AND ITS IMPORTANCE IN THE DESCRIPTION OF THE DRAWING (Archive of Conferences, 2022)
Perspective is an art technique for creating an illusion of three-dimensions (depth and space) on a two-dimensional (flat) surface. Perspective is what makes a painting seem to have form, distance, and look “real”. The same rules of perspective apply to all subjects, whether it's a landscape, seascape, still life, interior scene, portrait, or figure painting.